PELATIHAN PENGOLAHAN DATA PENJUALAN MENGGUNAKAN MICROSOFT EXCEL PADA UMKM - Adha, Afifah Cahayani; Hendriani, Sisi; Nelaz, Yolanda Safitri (LPPM Universitas Awal Bros, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the Indonesian economy. The contribution of MSMEs to Gross Domestic Product (GDP) and employment is very significant, so that the sustainability and development of this sector has become a priority in various government policies. However, despite their important role, many MSMEs face various obstacles in managing their business, especially in terms of processing and analyzing sales data. One of the main obstacles faced by MSMEs is limitations in data management capabilities. Accurate and structured sales data is a vital element in making the right business decisions. This data can be used to identify sales trends, measure product performance, plan marketing strategies, and optimize inventory. However, many MSME owners and managers do not have adequate skills or knowledge in managing sales data effectively. Microsoft Excel is a program whose main function is to process data in the form of numbers using spreadsheets in presenting rows and columns to execute orders. The aim of this community service activity is to assist MSMEs in processing sales data.